Pendekatan MapReduce untuk Implementasi Suffix Tree pada AutoComplete Produk dengan Metodologi Agile - Yosef Ariyanto Irawan; Billyanto Hendrik; Antonius Antonius; Taufan Abdurrachman; Arie Tunggal; Bernard Renaldy Suteja (Maranatha University Press, 2019)
With the development of technology and communication nowadays, it encourages everyone to get everything quickly, easily and precisely, especially in the world of e-commerce which is increasingly widespread and needed by almost everyone. A small thing that can help consumers is when they start looking for products or services that are according to their wishes quickly, easily and precisely along with them, assisted by other alternative choices. So when consumers want to type in the product they are looking for, they need to quickly search for synonyms. Autocomplete helps to do that by making search predictions based on the number of products previously purchased.